Pedagogy and Psychology of Modern Education - Prozorova M. N., Iliashenko L. K., Zvonova E. V., Ryzhova I. M., Ermakov V. P., Krasovskaia S. V., Iudin G. V., Eganov A. V., Bykov V. S., Vericheva O. N., Andrianova R. A., Akhmetvalieva M. G., Khoteeva R. I. (Pedagogy and Psychology of Modern Education, 2022)
the article is deboted to the psychology of art which as a non-classical psychology focuses its attention on the means that a person develops and uses in his communication with the outside world, and implements it as a means of controlling his own psyche. The symbolic psychology of art studies the development, functioning and evolution of sign-symbolic systems at the level of interaction «man – man – society», since art in a widely accessible form is able to raise the most complex existential problems, as well as concentrate on the inner world of each person. The symbolic psychology of art, thanks to the active development of related sciences, primarily semiotics and art history, currently has great chances for productive development.
Keywords: символ; symbol; художественный образ; artistic image; образ мира; психология искусства; кросс-культурная коммуникация; культурные коды; уровни кодирования; системы художественного языка; средства взаимодействия; psychology of art; cross cultural communication; cultural codes; coding levels; systems of artistic language; means of interaction; image of the world